Humidity levels in soil in the onion bulbs production. - Estrada-Prado, Wilfredo (2015)
The aim of this study was to evaluate the effect of different soil humidity levels on the production of onion bulbs. Research was conducted at the Jorge Dimitrov Agricultural Research Institute, in the Bayamo municipality, Granma province, Cuba, during 2009-2010. Three soil moisture levels were evaluated: 100%, 75% and 50% of field capacity. Fifteen treatments and five varieties were used and were distributed in a complete randomized design. Twenty plants were selected at random from each treatment. The indicators that were evaluated in the bulbs were: mean weight (g), equatorial diameter (cm) and polar diameter (cm). Our results indicate that soil water deficit causes a significant reduction on bulbing size and bulbing mass, with the greater impact at 50% soil humidity.